Whitaker's almanack 2008 (Gale virtual reference library, 2007)
Brings together a wide range of facts, figures and directory information on current affairs and general knowledge. Contains a comprehensive overview of every aspect of United Kingdom infrastructure and an excellent introduction to world politics.